Embedded PC based wireless communication using XTEA - Khok, Jess Lyn (2010)
This project presents an embedded cryptosystem for PC based wireless communication using the XTend OEM RF modules. It focuses mainly on cryptography and its implementation in an embedded system. The Extended Tiny Encryption Algorithm (XTEA) is the chosen encryption method. This is due to the fact that it is a cryptographic algorithm designed to minimize memory footprint and maximize speed. Being flexible and fast in software, XTEA is fast in hardware as well. A Graphical User Interface (GUI) is designed for the application whereby the user communicates with another user through it. It is able to send and also display the data exchange between two PC users. When data is entered in one of the PC, the PIC18F14K50 microcontroller encrypts the data before it is transmitted wirelessly from one PC to another through the XTend OEM RF modules. The ciphertext is then received by the XTend OEM RF module at the other PC but will remain encrypted unless the receiver inputs the correct key. This key is used to decrypt the ciphertext into its original data. When the receiver from the other PC enters the correct key, the ciphertext will be decrypted by the PIC18F15K50 microcontroller and the original data will be displayed in the GUI. The resultant hardware is two sets of identical cryptography wireless module which are able to perform both the encryption and decryption process, connected to the GUI in two different PC. This project produces a secure mean for safe wireless communication on PC level